A research on informal technology transfer channels between universities and companies - international experience and implications for Vietnam - Le Minh Hai; Phung Le Duy; Chu Van Tung; Cao Minh Duc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
The transfer of technology has become one of the primary activities of universities today, and research on informal technology transfer channels is essential. However, there has not been a formal study on this in Vietnam. This research aims to aggregate and analyze the activities, and influencing factors of informal technology transfer, providing a comprehensive overview of informal knowledge transfer channels and the factors impacting them. This will help expand the guidance and management capabilities of technology transfer at Vietnamese universities. The study involves synthesizing in-depth research materials on informal technology transfer channels from universities, combined with expert interviews. The results of the study will clarify prevalent informal technology transfer channels in various fields such as pharmaceuticals, robotics, and factors influencing these informal channels. These factors include scientists‘ motivations for transfer, relationships, personal networks with businesses, technology readiness, and university-business transfer policies. Through this research, a better understanding of informal knowledge transfer channels will be established, creating opportunities to optimize knowledge transfer and promote scientific and technological development within the university environment in Vietnam. Code: 23092201